In vitro Mass Propagation of Cymbidium aloifolium (L.) Sw. (Plant Tissue Culture and Biotechnology, 2019)
Cymbidium aloifolium (L.) Sw. is an epiphytic orchid distributed locally in Bangladesh. Natural populations of this orchid are under threat due to its high commercial value in the floriculture industry by over exploitation. Mass propagation provides an alternative means of satisfying the demand. In this study, half strength of MS supplemented with BAP or different combinations with NAA was evaluated for seed germination and early protocorm development of C. aloifolium (L.) Sw. The maximum percentage of seed germination (98) was obtained on modified MS (half strength of micro and macro nutrients and full strength of vitamin) supplemented with 0.5 mg/l BAP and 0.5 mg/l NAA after three weeks of culture. Maximum number of shoots (9.6 shoots per single shoot) were developed from shoot tip explants on half strength of MS supplemented with 1.0 mg/l BAP and 0.5 mg/l NAA. The most effective auxin source promoting root production (3.2 roots per shoot) was 1.0 mg/l IBA in combination with 0.5 mg/l BAP. The seedlings were successfully acclimatized (survival percentage 99) in a nethouse using a rooting medium of crushed sterile brick, cocopit and charcoal (1 : 1 : 1 v/v).Plant Tissue Cult. & Biotech. 29(1): 73-79, 2019 (June)